A Blossoming of Oranges: Dueling Houses of Criticism and the Creative Writing Workshop Model—An Existential Phenomenological Response. (July 2016) - Howe, Lori
"A Blossoming of Oranges" is a phenomenological response to two houses of criticism of the creative writing workshop model, the first of which positions the workshop model as a force for cultural hegemony, and the second of which identifies the workshop model as a causal factor for the deterioration of writing in America. This defense is presented in the form of theatrical vignettes, participant writing, and constructed conversations between participants, researcher, and critics. Major lines of criticism are explored, as well as the bodies of research on both the creative writing workshop model and the field of existential phenomenology, as they illuminate the workshop model as an aesthetic hermeneutic that may aid in the artistic development of individuals and the betterment of society.